CHRISTIANITY AND ISLAM: MORISCOES OF GRANADA IN THE LANDS OF TOLEDO. - Sánchez González, Ramón (Revista de Historia Social y de las Mentalidades, 2024)
The aim of this paper is to analyze the relationships between the Moriscoes of Granada and the old Christians in a particular place, the Kingdom of Toledo, within the more generic framework of the Crown of Castile. To that end, a plurality of documentary sources, some of them very rare indeed, has been used. The most significant outcome is the fact that in this area co-existence can be described as peaceful, cordial, obviously not exempt from some conflicts, but never due to their condition of social or ethnic minority. Moreover, in no case does the argument of being a group unable to integrate into society seem to be appropriate to justify their expulsion from the area considered in this study.